Mini health carnival - Mohd Firdaus, Muhammad Abbas; Mohd Zuki, Abdul Hadi; Hassan, Mohammad Syafiq; Chen, Xin Wee (Faculty of Medicine, 2022)
On 21 August 2022, in collaboration with Majlis Perwakilan Penduduk (MPP) Zon 15, Majlis Bandaraya Shah Alam (MBSA), a Mini Health Carnival program was successfully conducted by 54 fourth-year UiTM Bachelor of Medicine students undergoing the posting of Population Health and Preventive Medicine to promote health to the community. The program took place in the MBSA Hall, Kampung Sungai Kandis, Seksyen 36, Shah Alam, Selangor. This carnival, themed ‘Kurang Gula Hidup Bahagia’, aimed to raise awareness and educate the community about non-communicable diseases such as Type 2 diabetes mellitus, high blood pressure, and dyslipidemia.